The effects of activity-related contexts on individual sound exposures: A time–geographic approach to soundscape studies. (September 2021) - Kou, Lirong; Kwan, Mei-Po; Chai, Yanwei
Noise is an ever-growing problem in cities. Conventional noise mitigation approaches may not necessarily control noise pollution, since whether a sound is perceived as noise is largely influenced by its specific contexts. Based on an activity-centric framework, this study examines the effects of activity-related contexts and measured sound levels based on individuals' sound evaluations as they undertake daily activities at different geographic locations and times. Data for the study were collected from 33 participants in Chicago (USA) using Global Positioning System-equipped mobile phones, portable sound sensors, and activity diaries. Multilevel logistic modeling was used to examine the relationships among measured sound levels, sound evaluations, and activity-related contexts for each recorded activity of the participants. The results indicate that activity-related contexts significantly influence individuals' sound evaluations as they perform their daily activities. When activity-related contexts are taken into account, the measured sound levels that individuals experienced when performing an activity are no longer significant in influencing their sound evaluations. These results support the notion that sound is not only a physical feature but also a socio-psychological construct. It is crucial to adopt a human-centric and context-aware approach in urban planning through understanding the circumstances in which a sound is perceived as noise. Such an approach would help improve sound-related urban environments and construct livable and healthy cities.